Examining risk factors for cardiovascular disease among food bank members in Vancouver - Fowokan, A.O. (Prev Med Rep, 2018)
Food banks provide supplemental food to low-income households, yet little is known about the cardiovascular health of food banks members. This study therefore described cardiovascular disease (CVD) risk factors among food bank members and explored associations between food insecurity and CVD risk. Adults ≥18 years (n = 77) from three food bank sites in metro Vancouver, British Columbia completed surveys and physical assessments examining a range of socio-demographic variables and CVD risk factors. A composite measure of myocardial infarction (MI) risk called the INTERHEART score was assessed and household food insecurity was measured using the Household Food Security Survey Module. Regression models were used to explore associations between food insecurity and CVD risk measures, including the INTERHEART score. Ninety-seven percent of food bank members reported experiencing food insecurity, 65% were current smokers, 53% reported either chronic or several periods of stress in the past year, 55% reported low physical activity levels and 80% reported consuming fewer than five servings of fruit and vegetables daily. Prevalence of self-reported diabetes and hypertension were 13% and 29% respectively. Fifty-two percent of the sample were at high risk of non-fatal MI. No statistically significant associations were found between increased severity of food insecurity and CVD risk factors among this sample where both severe food insecurity and high CVD risks were prevalent. Food bank members were at elevated risk for CVD compared with the general population. Strategies are needed to reduce prevalence of food insecurity and CVD risk factors, both of which disproportionately affected food bank members.